194. Antimicrobial Susceptibility Data of Staphylococcus lugdunensis After the Implementation of Rapid Molecular Blood Culture Diagnostics (Verigene® Gram-Positive Blood Culture Nucleic Acid Test). (4th December 2021) - Constance, Kristin; Hunt, Alauna; Karimaghaei, Sam; Chijioke, Juliet; Chavez, Violeta; Wanger, Audrey; Masayuki, Nigo
Abstract: Background: S. lugdunensis is a coagulase negative staphylococci (CoNS) demonstrating high level pathogenicity. In contrast to other CoNS, S. lugdunensis (SL ) remains susceptible to most antibiotics. Prior to the implementation of Verigene®, SL was identified by provider request only. We sought to describe the susceptibility data of SL isolated from blood culture after the implementation of multiplex PCR, as well as to determine the correlation of the mecA gene provided by Verigene® and oxacillin resistance. Methods: Retrospective review of all blood culture isolates positive for SL from two major hospital systems, Memorial Hermann Hospital System (14 hospitals) and HarrisHealth System (two acute care hospitals) identified on Verigene® PCR. Multiple isolates detected from the same patients were excluded from this analysis. Memorial Hermann utilized Microscan®, and HarrisHealth utilized BD Phoenix® for susceptibility testing. Results: Between 2017 – 2021, 157 patients were identified with SL positive blood cultures. Of them, 141 isolates had susceptibility data collected, which is summarized in table 1. Resistance rates were highest amongst clindamycin 97/141 (68.8 %) susceptible, erythromycin 98/141 (69.5%) susceptible, and oxacillin 120/141 (85.1%) susceptible. 127/141 (90.1%) of isolates were tested for mecA on Verigene®. 13 of 21 oxacillin resistant isolates were from pure culture, of these isolates, none had mecA detected. Conclusion: In our study, clindamycin and erythromycin demonstrated similar susceptibility compared to prior studies in the literature, however oxacillin susceptibility rate was lower than expected at 85.1%, compared to 95.3% in a prior large-scale United States based study in 2017. Absence of mecA gene detection on multiplex PCR did not correlate with oxacillin susceptibility suggesting that oxacillin susceptibility cannot be accurately predicted by the use of multiplex PCR systems, such as Verigene®, as demonstrated in Table 2. Our study also suggested that increased prevalence of oxacillin resistant SL isolates may be emerging. Disclosures: All Authors : No reported disclosures